2006
DOI: 10.1097/01.hpc.0000202248.77279.69
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Hospital Care Improvement Strategies Reduce Time to Treatment in ST-Elevation Acute Myocardial Infarction

Abstract: Implementation of HCIS shortened door-to-PCI time for patients with STEMI by 39.2 +/- 10 minutes. Thus, HCIS may be effective in improving patient outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Quality assurance, realtime feedback, and healthcare provider education can also reduce the time to therapy in STEMI. 89,[93][94][95][96][97] Involvement of hospital leadership in the process and commitment to support rapid access to STEMI reperfusion therapy are critical factors associated with successful programs.…”
Section: Systems Of Carementioning
confidence: 99%
“…Quality assurance, realtime feedback, and healthcare provider education can also reduce the time to therapy in STEMI. 89,[93][94][95][96][97] Involvement of hospital leadership in the process and commitment to support rapid access to STEMI reperfusion therapy are critical factors associated with successful programs.…”
Section: Systems Of Carementioning
confidence: 99%
“…Care processes associated with shorter door to balloon times are presented in Table 4 and include: ER physician activates cath lab (including several variations) [80,[82][83][84]88,93,95,100], single call to a central page to activate cath lab [78,100], requiring that staff arrive within 20 min of page [100], ER activating cath lab while patient is en route [100], ER and cath lab receiving real time feedback [100], attending cardiologist always on site [100], passive monitoring of physician performance [92], obtaining a pre-hospital ECG (including several variations) [15,16,23,25,29,35,37,57,63,64,77,97], initial culprit vessel PCI before full diagnostic angiography [19,46] and initiation of a quality improvement initiative or critical pathway [17,79,87,[89][90][91]94,96,99]. Longer times are reported with improperly low initial triage of emergency patients with STEMI [66] and use of an intraaortic balloon pump [5].…”
Section: Care Processesmentioning
confidence: 99%
“…662,663 Twelve studies demonstrated that emergency physician activation of the catheterization laboratory was associated with significant reductions in door-to-balloon time intervals (20 to 68 minutes) (LOE 2 664 -666 ; LOE 3 [667][668][669][670][671][672][673] ; LOE 5 663,674 ). Falsepositive activation rate in these studies ranged from 0% to 15%.…”
Section: Consensus On Science Emergency Physician or Prehospital Actimentioning
confidence: 99%
“…Falsepositive activation rate in these studies ranged from 0% to 15%. 674,[663][664][665][666][667][668][669][670][671][672][673] Prehospital Activation of the Catheterization Laboratory. Seven studies demonstrated the effectiveness of prehospital activation on reducing door-to-balloon time intervals (22 to 69 minutes) (LOE 2 656,675 ; LOE 3 676,677 ; LOE 4 660,678 ).…”
Section: Consensus On Science Emergency Physician or Prehospital Actimentioning
confidence: 99%